Alginic acid cell entrapment: a novel method for measuring in vivo macrophage cholesterol homeostasis - Timothy J. Sontag; Bijoy Chellan; Clarissa V. Bhanvadia; Godfrey S. Getz; Catherine A. Reardon (Journal of Lipid Research, 2015)
Macrophage conversion to atherosclerotic foam cells is partly due to the balance of uptake and efflux of cholesterol. Cholesterol efflux from cells by HDL and its apoproteins for subsequent hepatic elimination is known as reverse cholesterol transport. Numerous methods have been developed to measure in vivo macrophage cholesterol efflux. Most methods do not allow for macrophage recovery for analysis of changes in cellular cholesterol status. We describe a novel method for measuring cellular cholesterol balance using the in vivo entrapment of macrophages in alginate, which retains incorporated cells while being permeable to lipoproteins. Recipient mice were injected subcutaneously with CaCl2 forming a bubble into which a macrophage/alginate suspension was injected, entrapping the macrophages. Cells were recovered after 24 h. Cellular free and esterified cholesterol mass were determined enzymatically and normalized to cellular protein. Both normal and cholesterol loaded macrophages undergo measureable changes in cell cholesterol when injected into WT and apoA-I-, LDL-receptor-, or apoE-deficient mice. Cellular cholesterol balance is dependent on initial cellular cholesterol status, macrophage cholesterol transporter expression, and apolipoprotein deficiency. Alginate entrapment allows for the in vivo measurement of macrophage cholesterol homeostasis and is a novel platform for investigating the role of genetics and therapeutic interventions in atherogenesis.